If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -1(x + 3) + 6x = 0 Reorder the terms: -1(3 + x) + 6x = 0 (3 * -1 + x * -1) + 6x = 0 (-3 + -1x) + 6x = 0 Combine like terms: -1x + 6x = 5x -3 + 5x = 0 Solving -3 + 5x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '3' to each side of the equation. -3 + 3 + 5x = 0 + 3 Combine like terms: -3 + 3 = 0 0 + 5x = 0 + 3 5x = 0 + 3 Combine like terms: 0 + 3 = 3 5x = 3 Divide each side by '5'. x = 0.6 Simplifying x = 0.6
| 23-x=17 | | 9x^2-17=-16 | | -7(1+4x)=217 | | 6x+9=4x+25 | | 8-7j=-6j | | 12+1y+3y=28 | | (2x-1)/3=5x-6/4 | | 2x-9=3x+0 | | 4=-2(4.50+25p) | | -32-8x+6x=12 | | -3(w+1)-4= | | 58=3x+4x+2 | | p=5+2q | | 4=-2(4.50+25) | | 3X*2-12X=2X+7 | | 19+169r^2=380 | | 2.1x-2.16=0.84-5.4 | | 5w=6w-8 | | 5x+2x-6=43 | | 3(2u-3)-2(u+4)= | | 5p^2-17=28 | | f(x)=x-26 | | -400=8(-8b+6) | | 9(-39/2)-5((-39/2)-6) | | 5(w+6)-7w= | | 5x/5x^3 | | 9(-39/2)-5((-39/2)-6 | | 7v^2-3=4 | | -7x+9-4x=130 | | -10-6x+2x=-22 | | 5x^3/5x= | | 10.7w+4=57.87 |